Practical industrial data networks : design, installation and troubleshooting - Mackay, Steve (Practical professional books from Elsevier., 2004)
There are many data communications titles covering design, installation, etc, but almost none that specifically focus on industrial networks, which are an essential part of the day-to-day work of industrial control systems engineers, and the main focus of an increasingly large group of network specialists. The focus of this book makes it uniquely relevant to control engineers and network designers working in this area. The industrial application of networking is explored in terms of design, installation and troubleshooting, building the skills required to identify, prevent and fix common industrial data communications problems - both at the design stage and in the maintenance phase. The focus of this book is 'outside the box'. The emphasis goes beyond typical communications issues and theory to provide the necessary toolkit of knowledge to solve industrial communications problems covering RS-232, RS-485, Modbus, Fieldbus, DeviceNet, Ethernet and TCP/IP. The idea of the book is that in reading it you should be able to walk onto your plant, or facility, and troubleshoot and fix communications problems as quickly as possible. This book is the only title that addresses the nuts-and-bolts issues involved in design, installation and troubleshooting that are the day-to-day concern of engineers and network specialists working in industry. * Provides a unique focus on the industrial application of data networks * Emphasis goes beyond typical communications issues and theory to provide the necessary toolkit of knowledge to solve industrial communications problems * Provides the tools to allow engineers in various plants or facilities to troubleshoot and fix communications problems as quickly as possible.